Oxidative stress, inflammation, and peritoneal dialysis: A molecular biology approach. Issue 10 (15th June 2021) - Innico, Georgie; Gobbi, Laura; Bertoldi, Giovanni; Rigato, Matteo; Basso, Anna; Bonfante, Luciana; Calò, Lorenzo A.
Abstract: The key role of oxidative stress (OxSt) and inflammation for the induction of cardiovascular disease, the leading cause of excess morbidity/mortality in chronic kidney disease and dialysis patients, is known and both the activations of NADPH oxidase and RhoA/Rho kinase (ROCK) pathway are pivotal for their effects. While specific hemodialysis procedures, such as hemodiafiltration with on‐line reinfusion of ultrafiltrate and/or the use of vitamin E‐coated dialyzers, are beneficial for OxSt and inflammation, studies in peritoneal dialysis (PD) are instead scarce and results seem not favorable. In nine patients under PD OxSt in terms of mononuclear cell protein level of p22 phox (Western blot), subunit of NADPH oxidase, essential for the generation of OxSt, and MYPT‐1 phosphorylation state (Western blot), a marker of ROCK activity, have been measured at the beginning and after 3 and 6 months of PD. Blood levels of interleukin 6 (IL‐6), ferritin, and albumin have been considered for evaluating the inflammatory state. p22 phox protein expression, MYPT‐1‐phosphorylation, and ferritin level were increased both at baseline vs healthy subjects ( P  = .02, P  < .0001, P  = .004, respectively) and vs baseline after 3 and 6 months of peritoneal dialysis ( P  = .007, P  < .001, P  = .004, respectively). Albumin was lower after 6 months of PD ( P  = .0014). IL‐6 was increased at baseline vs reference values and remained unchanged at 3 and 6 months. OxSt and inflammation increase during PD confirming via molecular biology approach a report at biochemical level. To improve OxSt state in PD, a multitarget approach is necessary. It might include the use of more physiologic pH, low glucose degradation products, low lactate and iso‐osmolar PD solutions, patients' strict glycemic control, optimal volume management, and antioxidant administration, such as N‐acetylcysteine. Abstract : Oxidative stress (OxSt) and inflammation increase during peritoneal dialysis (PD) confirming via molecular biology approach a biochemical report. They may lead to structural/functional damage of the peritoneal membrane, in addition to increase cardiovascular risk, the leading cause of excess morbidity/mortality in dialysis patients.To improve OxSt in PD a multitarget approach is necessary. It might include the use of more physiologic pH, low glucose degradation products, low lactate and iso‐osmolar PD solutions, patients' strict glycemic control, optimal volume management.Studies in our laboratory are ongoing to evaluate with a molecular biology approach in PD patients, the effect of more biocompatible solutions on OxSt and its signaling.